THE IMPORTANCE OF VOICE NARRATION IN LEARNING THE ALPHABET THROUGH THE SCRATCH PROGRAM AND DEVELOPING THE IMAGINATION OF PRIMARY SCHOOL STUDENTS (British Journal of Global Ecology and Sustainable Development, 2025)
The article explores the possibilities of developing students' imagination and creative thinking skills through voice integration in learning using the "Scratch" programming language. Encouraging students to animate and practice the pronunciation of alphabet letters enhances their comprehension and retention. By utilizing these letters to find similarities in meaning and structure, identify differences between words, create meanings from initial letters, and play games like "find the letter" or pictorial puzzles, along with visualizing games through scripts on stage, students' imagination is stimulated. This method effectively supports the assimilation of creative thinking techniques such as analogy, comparison, and generalization.